Assessment of total coliforms and E. coli removal in algae-based pond under tropical temperature in addition of carbon dioxide (CO2) and shading - Pompei, Caroline Moço Erba [UNESP]; Ruas, Graziele [UNESP]; Bolzani, Hugo Renan [UNESP]; Silva, Gustavo Henrique Ribeiro da [UNESP] (Elsevier, 2023)
The present work aimed to investigate the effects of adding CO2 to the treatment carried out by native microalgae in a raceway pond with high load sewage to remove E. coli and total coliforms, as well as to evaluate the influence of shading on the treatment system operated on a pilot scale, outdoors under actual conditions in real time analysis. There were significant correlations between total coliforms and E. coli removals with abiotic parameters such as pH and dissolved oxygen. From the results, it was observed that in the experiments without shading the removal of total coliforms and E. coli were better. It can be concluded that they were factors acting synergistically for the success of the pathogenic removal of coliforms and this may be the occurrence of endogenous photo-oxidation and oxidative stress in microbial cell leads to DNA damage and cell death due inactivate the metabolic growth of the cells. Further, the final effluent generated by the pond cannot be used for direct reuse, a post-treatment is necessary to fit within the established limits so as to increase the possibilities of its reuse.
Keywords: E. coli and total coliforms removals; Microalgae; Photooxidation; Raceway pond